2016
DOI: 10.1007/s00705-016-3130-2
|View full text |Cite
|
Sign up to set email alerts
|

Roles of reactive oxygen species in cell signaling pathways and immune responses to viral infections

Abstract: Several biological processes as well as infectious agents, physiological or environmental stress, and perturbed antioxidant response can promote oxidative stress. Oxidative stress usually happens when cells are exposed to more electrically charged reactive oxygen species (ROS) such as HO or O. ROS are well known for being both beneficial and deleterious. Recent studies have indicated that ROS are deleterious to cells, leading to programmed cell death (PCD) at high concentrations. At low concentrations, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 60 publications
0
80
0
Order By: Relevance
“…) and virus‐induced ROS generation is linked to the activation of different signalling molecules and transcription factors, such as NF‐κB, signal transducer and activator of transcription (STAT) proteins (STAT1, STAT3), and Janus kinase (JAK2) (Li et al . ). Generation of oxidative stress during viral infection or replication may play a key role in the development and progression of many pathological conditions (Li et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…) and virus‐induced ROS generation is linked to the activation of different signalling molecules and transcription factors, such as NF‐κB, signal transducer and activator of transcription (STAT) proteins (STAT1, STAT3), and Janus kinase (JAK2) (Li et al . ). Generation of oxidative stress during viral infection or replication may play a key role in the development and progression of many pathological conditions (Li et al .…”
Section: Discussionmentioning
confidence: 97%
“…Generation of oxidative stress during viral infection or replication may play a key role in the development and progression of many pathological conditions (Li et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…It is known that susceptibility to viral infection is modulated by the redox environment . ROS play a central role in the determination of second messengers in a cell to modify various signaling molecules.…”
Section: Resultsmentioning
confidence: 99%
“…ROS play a central role in the determination of second messengers in a cell to modify various signaling molecules. The EV71‐induced generation of ROS is essential for viral replication in host cells . A previous study suggested that EV71 infection induces mitochondrial ROS generation, which in turn promotes viral replication .…”
Section: Resultsmentioning
confidence: 99%
“…During normal phenomena of catabolism and aerobic respiration, there is a partial reduction of oxygen to form hyperactive radicals such as superoxide radical, hydrogen peroxide, hydroxyl radical, and peroxyl radical which are grouped as reactive oxygen species (ROS) . The limited dose of these reactive intracellular signals is beneficial in various biological responses in order to maintain homeostasis . However, the overproduction of ROS due to failure in antioxidant defense system are detrimental for cells and tissues as it causes oxidative stress and damage to DNA, proteins, membrane lipids, and lipoproteins .…”
Section: Introductionmentioning
confidence: 99%